Dual-energy perfusion-CT of pancreatic adenocarcinoma - Klauß, Miriam; Stiller, Wolfram; Pahn, Gregor; Fritz, Franziska; Kieser, Meinhard; Werner, Jens; Kauczor, Hans-Ulrich; Grenacher, Lars (European journal of radiology, 2013)
Purpose - To evaluate the feasibility of dual-energy CT (DECT)-perfusion of pancreatic carcinomas for assessing the differences in perfusion, permeability and blood volume of healthy pancreatic tissue and histopathologically confirmed solid pancreatic carcinoma. - Materials and methods - 24 patients with histologically proven pancreatic carcinoma were examined prospectively with a 64-slice dual source CT using a dynamic sequence of 34 dual-energy (DE) acquisitions every 1.5s (80ml of iodinated contrast material, 370mg/ml, flow rate 5ml/s). 80kVp, 140kVp, and weighted average (linearly blended M0.3) 120kVp-equivalent dual-energy perfusion image data sets were evaluated with a body-perfusion CT tool (Body-PCT, Siemens Medical Solutions, Erlangen, Germany) for estimating perfusion, permeability, and blood volume values. Color-coded parameter maps were generated. - Results - In all 24 patients dual-energy CT-perfusion was. All carcinomas could be identified in the color-coded perfusion maps. Calculated perfusion, permeability and blood volume values were significantly lower in pancreatic carcinomas compared to healthy pancreatic tissue. Weighted average 120kVp-equivalent perfusion-, permeability- and blood volume-values determined from DE image data were 0.27±0.04min−1 vs. 0.91±0.04min−1 (p<0.0001), 0.5±0.07 *0.5min−1 vs. 0.67±0.05 *0.5min−1 (p=0.06) and 0.49±0.07min−1 vs. 1.28±0.11min−1 (p<0.0001). Compared with 80 and 140kVp the standard deviations of the kVp120kVp-equivalent values were manifestly smaller. - Conclusion - Dual-energy CT-perfusion of the pancreas is feasible. The use of DECT improves the accuracy of CT-perfusion of the pancreas by fully exploiting the advantages of enhanced iodine contrast at 80kVp in combination with the noise reduction at 140kVp. Therefore using dual-energy perfusion data could improve the delineation of pancreatic carcinomas.